Demographic and Dietary Associations of Chronic Diarrhea in a Representative Sample of Adults in the United States. (April 2018) - Singh, Prashant; Mitsuhashi, Shuji; Ballou, Sarah; Rangan, Vikram; Sommers, Thomas; Cheng, Vivian; Iturrino‐Moreda, Johanna; Friedlander, Daniel; Nee, Judy; Lembo, Anthony
Abstract : OBJECTIVES: No studies to date estimate the prevalence of chronic diarrhea in the United States using the Bristol stool form scale (BSFS). This study aims to report the prevalence and associated factors of chronic diarrhea using BSFS scores in a nationally representative sample of US adults. METHODS: We identified 5, 246 adult participants (age ≥20 years) who completed the bowel health questionnaire in the National Health and Nutrition Examination Survey 2009–2010 data set. Chronic diarrhea was defined as type 6 or 7 rating on the BSFS (mushy or liquid consistency) as the "usual or the most common stool type." Co‐variables included age, race, education, poverty income ratio, body mass index, number of medications, feeling depressed, physical activity, and dietary intake. Prevalence estimates and prevalence odds ratios (PORs) were analyzed in adjusted multivariable models using appropriate sampling weights. RESULTS: We found a prevalence of chronic diarrhea of 6.6% (95% confidence interval (CI) 5.8, 7.4) in the nationally representative data set. High daily carbohydrate intake (POR 1.56, 95% CI 1.02, 2.40), obesity (POR 2.04, 95% CI 1.44, 2.89), feeling depressed (POR 1.84, 95% CI 1.21, 2.80), older age (POR 1.02, 95% CI 1.01, 1.02), and female sex (POR 1.68, 95% CI 1.28, 2.21) were positively correlated with chronic diarrhea. Non‐Hispanic White race (POR 0.49, 95% CI 0.29, 0.81) and higher education (POR 0.60, 95% CI 0.43, 0.83) were negatively correlated with chronic diarrhea. CONCLUSIONS: In a nationally representative sample of the US adults, the prevalence of chronic diarrhea was 6.6%. We identified demographic, lifestyle, and dietary factors associated with chronic diarrhea.